Improved Constraints on Global Methane Emissions and Sinks Using δ13C‐CH4. Issue 6 (17th June 2021) - Lan, X.; Basu, S.; Schwietzke, S.; Bruhwiler, L. M. P.; Dlugokencky, E. J.; Michel, S. E.; Sherwood, O. A.; Tans, P. P.; Thoning, K.; Etiope, G.; Zhuang, Q.; Liu, L.; et al.
Abstract: We study the drivers behind the global atmospheric methane (CH4 ) increase observed after 2006. Candidate emission and sink scenarios are constructed based on proposed hypotheses in the literature. These scenarios are simulated in the TM5 tracer transport model for 1984–2016 to produce three‐dimensional fields of CH4 and δ 13 C‐CH4, which are compared with observations to test the competing hypotheses in the literature in one common model framework. We find that the fossil fuel (FF) CH4 emission trend from the Emissions Database for Global Atmospheric Research 4.3.2 inventory does not agree with observed δ 13 C‐CH4 . Increased FF CH4 emissions are unlikely to be the dominant driver for the post‐2006 global CH4 increase despite the possibility for a small FF emission increase. We also find that a significant decrease in the abundance of hydroxyl radicals (OH) cannot explain the post‐2006 global CH4 increase since it does not track the observed decrease in global mean δ 13 C‐CH4 . Different CH4 sinks have different fractionation factors for δ 13 C‐CH4, thus we can investigate the uncertainty introduced by the reaction of CH4 with tropospheric chlorine (Cl), a CH4 sink whose abundance, spatial distribution, and temporal changes remain uncertain. Our results show that including or excluding tropospheric Cl as a 13 Tg/year CH4 sink in our model changes the magnitude of estimated fossil emissions by ∼20%. We also found that by using different wetland emissions based on a static versus a dynamic wetland area map, the partitioning between FF and microbial sources differs by 20 Tg/year, ∼12% of estimated fossil emissions. Key Points: Increased fossil fuel emissions are unlikely the dominant driver for post‐2006 global CH4 increase A significant decrease in the abundance of hydroxyl radicals (OH) cannot explain the post‐2006 global CH4 increase CH4 emission attributions are sensitive to the uncertainties in OH fractionation, tropospheric Cl sink, and wetland areas